A Nationwide Survey of Peer Review Practices in Child Maltreatment Teams. (13th September 2014) - Greeley, Christopher; Yoon, Jaennie; Tran, Xuan; Giardino, Angelo
Abstract : Medical evaluations for suspected child sexual abuse carry a significant medico‐legal burden and are often performed in a variety of clinical settings, by clinicians with different levels of expertise and experience. Peer review or professional practice evaluation is an important component for quality assurance. We surveyed 255 programmes which provided sexual abuse evaluations which were identified through queries with national child abuse professional organisations. We sought information on team composition and setting, patient population characteristics and each site's peer review process. Of the 129 responding programmes, 42 per cent (n = 44) reported having a written peer review process. There were no differences between practice types with regards to having a written peer review process, the percentage of cases reviewed, the documentation type reviewed or the percentage reporting an external review process. The majority of programmes (n = 89, 85%) reported that they review both chart and photo documentation during the peer review process. Our data support that most programmes involved in child maltreatment evaluations undergo some form of peer review, but there exists a large amount of heterogeneity in the process by which it occurs. Copyright © 2014 John Wiley & Sons, Ltd. 'We surveyed 255 programmes which provided sexual abuse evaluations' Key Practitioner Messages: Peer review is an important process to ensure high quality of clinical practice. The majority (80%) of programmes which perform child sexual abuse evaluations reported performing some form of peer review. Most peer review involves both chart and photo documentation reviews. 'Most peer review involves both chart and photo documentation reviews'